Preparation method of zwitterion co-doping optimized stannous selenide thermoelectric material

Through the optimized preparation method of stannous selenide thermoelectric material with anion and cation co-doping, the problem of insufficient preparation of n-type materials of tin selenide-based thermoelectric material is solved, significantly improving its thermoelectric performance and achieving efficient thermoelectric conversion effect.

CN119836210APending Publication Date: 2025-04-15KUNMING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510019655.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, n-type materials of tin selenide-based thermoelectric materials are insufficiently prepared, resulting in poor thermoelectric performance, especially high thermal conductivity of the lattice, which affects the optimization and regulation of thermoelectric performance.

Method used

The preparation method of stannous selenide thermoelectric material optimized by co-doping of anion and cations is adopted to regulate the types and concentration of doped ions through co-doping of Zr4+ and Cl-ion, and optimize the electrical transport performance and thermal conductivity of tin selenide materials.

Benefits of technology

The electrical transport performance and thermoelectric performance of n-type polycrystalline tin selenide are significantly improved, the power factor is doubled, and the ZT value is as high as 1.42 at 773K, improving the stability and reliability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836210A_ABST
    Figure CN119836210A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of high-performance thermoelectric materials, and discloses a preparation method of an anion-cation co-doping optimized stannous selenide thermoelectric material, which comprises the following steps: step 1, firstly, in a glove box environment filled with helium, preparing a stannous selenide thermoelectric material with a stannous selenide structure according to the specific requirements of an experiment and an atomic mass ratio; the method comprises the following steps: accurately weighing a proper amount of tin powder, selenium powder and a doping agent-zirconium tetrachloride powder, carefully putting the raw materials into a high-purity quartz glass tube, and then carrying out double-layer vacuum sealing treatment on the quartz glass tube filled with the raw materials by using a vacuum tube sealing machine under the condition of extremely high vacuum degree, so as to obtain the high-purity tin-selenium-doped zirconium tetrachloride tube. Therefore, the reaction environment is pure and stable. According to the preparation method of the zwitterion co-doping optimized stannous selenide thermoelectric material, through zwitterion co-doping of Zr < 4 + > and Cl <->, the electrical transport performance, including the carrier concentration, the conductivity and the Seebeck coefficient, of n-type polycrystalline tin selenide is remarkably improved, and the power factor is doubled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-performance thermoelectric material preparation, and in particular to a method for preparing anion-cation co-doped optimized tin(II) selenide thermoelectric material. Background Art

[0002] Thermoelectric materials are a type of new energy functional materials that can directly and reversibly realize the mutual conversion between thermal energy and electrical energy. They play an irreplaceable role in the fields of temperature difference power generation and precise temperature control. In recent years, researchers have developed efficient and environmentally friendly tin-sulfur layered wide-bandgap thermoelectric materials (tin selenide, tin sulfide), which have significantly optimized and improved the thermoelectric performance of materials in a wide temperature range, triggering a wave of research on this type of wide-bandgap thermoelectric materials by researchers in the field of thermoelectrics. In addition, tin selenide-based thermoelectric materials have gained more extensive research focus due to their ability to obtain better thermoelectric performance than tin sulfide.

[0003] After in-depth research in the field of tin selenide thermoelectric materials, it was found that tin selenide crystals are essentially a p-type semiconductor, and past research has mainly focused on improving the thermoelectric properties of p-type tin selenide, and has made significant progress; however, the practical application of thermoelectric materials is inseparable from thermoelectric devices, and an efficient thermoelectric device system needs to be composed of two types of semiconductor devices with similar thermoelectric properties, n-type and p-type, made of the same material. Therefore, there is an urgent need to carry out research on the preparation of n-type tin selenide-based thermoelectric materials and the optimization and regulation of their thermoelectric properties.

[0004] According to existing research, the main reason for the poor intrinsic electrical transport performance of tin selenide is the large number of intrinsic defects in its matrix. These defects will scatter carriers, thus seriously affecting the transport of carriers. In order to solve this problem, an effective optimization strategy can be adopted: first, by regulating and optimizing the intrinsic defect concentration and carrier concentration, the electrical transport performance of tin selenide can be improved; at the same time, multi-scale defects are introduced to enhance phonon scattering, thereby significantly reducing the lattice thermal conductivity. These two methods work synergistically to optimize the thermoelectric properties of tin selenide. Therefore, a method for preparing tin selenide thermoelectric materials optimized by anion and cation co-doping is proposed to solve the above-mentioned problems. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material, which has the advantages of accurately controlling the type and concentration of doped ions, achieving dual optimization of the electrical transport performance and thermal conductivity of the tin selenide material, and solving key problems such as the lack of n-type tin selenide-based thermoelectric materials, poor intrinsic electrical transport performance of tin selenide, high lattice thermal conductivity, and optimization and regulation of thermoelectric properties.

[0007] (II) Technical solution

[0008] In order to achieve the above-mentioned precise control of the type and concentration of doped ions and realize the dual optimization of the electrical transport performance and thermal conductivity of tin selenide materials, the present invention provides the following technical solution: a method for preparing anion-cation co-doped optimized tin selenide thermoelectric material, comprising the following steps:

[0009] Step 1: First, in a glove box filled with helium, according to the specific needs of the experiment and the atomic mass ratio, the appropriate amount of tin powder, selenium powder and dopant - zirconium tetrachloride powder are accurately weighed out. These raw materials are carefully placed in a high-purity quartz glass tube. Then, a vacuum tube sealer is used to perform a double-layer vacuum sealing process on the quartz glass tube containing the raw materials under extremely high vacuum conditions to ensure the purity and stability of the reaction environment;

[0010] Step 2: Then put the sealed quartz glass tube into a vertical muffle furnace. At high temperature, these raw materials will undergo a melt-solid phase reaction. When the preset melting program is completed, the sample can be allowed to gradually cool down to room temperature as the furnace cools. In this process, the raw materials will fuse and form a sample ingot doped with specific ions;

[0011] Step 3: Finally, the molten ingot is placed back into the glove box and manually ground into powder using an agate mortar. The particle size range of the powder is precisely controlled by sieving. Next, the powder is heat treated in an inert atmosphere (such as argon or nitrogen) to remove moisture and residual gas. Subsequently, a graphite mold with a suitable inner diameter is selected to perform spark plasma sintering on the pretreated powder. Finally, a graphite mold with a suitable inner diameter is selected, the ground powder is filled into it, and spark plasma sintering is performed to obtain a preliminary doping-optimized bulk tin selenide-based thermoelectric material.

[0012] Preferably, the chemical composition of the prepared n-type polycrystalline stannous selenide-based thermoelectric material consists of a mixture of SnSe and ZrCl4, specifically in the form of SnSe0.95+xwt%ZrCl4, wherein the value of x ranges from 0 to 1.

[0013] Preferably, in step one, the total weight of the raw materials is controlled between 10 and 20 grams, and the purity of the raw materials exceeds 99.9%. The raw materials need to be processed under high vacuum conditions during the vacuum sealing process, and the vacuum degree needs to be lower than or equal to 10^-2Pa.

[0014] Preferably, in step 1, during the high-temperature melt solid phase reaction stage, the reaction temperature is precisely controlled between 900 and 1000°C, the insulation time is between 20 and 30 hours, and the heating and cooling rate is controlled between 50 and 100°C / hour.

[0015] Preferably, in step 2, during the ingot processing stage after melt forming, the ingot needs to be manually ground using an agate mortar in a glove box, and the grinding time needs to be controlled between 10 and 30 minutes.

[0016] Preferably, in step three, the ground powder needs to be sieved to control its particle size range to be between 10 and 1000 nanometers, the inner diameter size range of the graphite mold used in the spark plasma sintering should be 10-20 mm, and the mold height size range should be 50-70 mm.

[0017] Preferably, in step three, the process parameters in the spark plasma sintering process need to be strictly controlled, the sintering temperature should be between 450 and 550°C, the applied pressure should be between 45 and 55 MPa, the heating rate should be between 50 and 100°C / minute, the sintering time should be between 10 and 15 minutes, and the sintering process should be carried out under a vacuum degree less than or equal to 10.0 Pa.

[0018] Preferably, in step three, the heat treatment temperature ranges from 100 to 300° C., and the insulation time ranges from 1 to 5 hours.

[0019] (III) Beneficial effects

[0020] Compared with the prior art, the present invention provides a method for preparing anion-cation co-doped optimized tin selenide thermoelectric material, which has the following beneficial effects:

[0021] 1. The method for preparing the tin selenide thermoelectric material optimized by anion and cation co-doping not only significantly improves the electrical transport properties of n-type polycrystalline tin selenide, including carrier concentration, electrical conductivity and Seebeck coefficient, and achieves a two-fold increase in power factor, but also effectively reduces the lattice thermal conductivity by introducing multi-scale defects and nanostructured second phase ZrSn, thereby achieving a double improvement in thermoelectric performance, and finally reaching a ZT value of up to 1.42 at 773K.

[0022] 2. The preparation method of the anion-cation co-doped optimized tin selenide thermoelectric material ensures the grain reorientation and orderly arrangement of the doped sample under high temperature, high pressure and high vacuum conditions by finely controlling the powder range and adopting the spark plasma sintering process, further optimizing the thermal transport properties and some mechanical properties; at the same time, the stabilizing effect of the ZrSn second phase reduces the deterioration effect of the second phase Sn on the tin selenide matrix, enhances the overall stability and reliability of the material, and provides strong support for the practical application of tin selenide thermoelectric materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the experimental process for preparing n-type polycrystalline tin selenide-based thermoelectric materials;

[0024] Figure 2 The data graphs are as follows: the electrical performance-related parameters of the n-type polycrystalline tin selenide-based thermoelectric materials prepared in Example 1 and Comparative Examples 1, 2, and 3 vary with temperature; Figure (a) is the electrical conductivity, Figure (b) is the Seebeck coefficient, Figure (c) is the power factor, and Figure (d) is the thermoelectric figure of merit ZT;

[0025] Figure 3 The figures are data graphs showing the variation of thermal performance-related parameters of n-type polycrystalline tin selenide-based thermoelectric materials prepared in Example 1 and Comparative Examples 1, 2, and 3 with temperature, wherein Figure (a) is the lattice thermal conductivity, Figure (b) is the total thermal conductivity, Figure (c) is the electronic thermal conductivity, and Figure (d) is a data graph showing the variation of actual density and theoretical density of samples of the Example and Comparative Example with different doping contents;

[0026] Figure 4 This is an energy spectrum diagram of the n-type polycrystalline tin selenide-based thermoelectric material prepared in Example 1;

[0027] Figure 5 The data graphs are of the changes of the electrical performance related parameters of the n-type polycrystalline tin selenide-based thermoelectric materials prepared in Examples 1, 2 and 3 with the temperature, wherein (a) is the conductivity, (b) is the Seebeck coefficient, (c) is the power factor, and (d) is the thermoelectric figure of merit ZT;

[0028] Figure 6 Data graphs showing the variation of electrical performance-related parameters of the n-type polycrystalline tin selenide-based thermoelectric materials prepared in Examples 1, 2, and 3 with temperature, with Figure (a) showing lattice thermal conductivity, Figure (b) showing total thermal conductivity, and Figure (c) showing electronic thermal conductivity. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1

[0031] A method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material, wherein the thermoelectric performance of the material is synergistically optimized through anion-cation co-doping, wherein the chemical composition molecular formula is SnSe_{0.95+x}wt%ZrCl_4, and when x is 0.5, it is represented as SnSe_{0.95+0.5}wt%ZrCl_4, and the specific preparation steps are as follows:

[0032] Step 1: In a glove box protected by helium, accurately weigh out high-purity raw materials: 9.0082 grams of tin powder (purity exceeding 99.999%), 5.9918 grams of selenium powder (purity exceeding 99.999%), and 0.075 grams of ZrCl_4 powder (purity exceeding 99.999%). After fully mixing these raw materials, put them into a double-layer high-purity quartz tube and seal them under the condition that the vacuum degree reaches or is lower than 10^-4Pa;

[0033] Step 2: Place the sealed quartz tube in a vertical muffle furnace, heat it to 950°C at a heating rate of 92.5°C / hour, and maintain it at this temperature for 24 hours for high-temperature melting solid phase reaction. After the reaction is completed, cool it to room temperature at the same cooling rate of 92.5°C / hour to obtain a melt-molded doped sample ingot;

[0034] Step 3: Then, in a glove box, the ingot is manually ground using an agate mortar for 20 minutes to break it into powder, and the particle size of the powder is controlled to be between 10 and 100 nanometers by sieving, and the powder is heat-treated under an inert atmosphere (such as argon or nitrogen);

[0035] Step 4: Finally, select a graphite mold with an inner diameter of 15 mm and a height of 60 mm, and perform spark plasma sintering on the treated doped sample powder at a sintering temperature of 500°C, an applied pressure of 50 MPa, a heating rate of 90°C / min, a sintering time of 13 minutes, and a sintering vacuum degree of 4.0 Pa or less. This step enables the powder grains to complete the re-orientation, orderly arrangement and recrystallization growth process in a high temperature, high pressure and high vacuum environment, and finally obtain a doped bulk tin selenide-based thermoelectric material.

[0036] In summary, the thermoelectric properties of tin selenide are effectively optimized by precisely controlling the ratio of raw materials and using ZrCl_4 for co-doping with anions and cations. The doped material shows better performance in terms of electrical conductivity, Seebeck coefficient and thermal conductivity, thereby improving its thermoelectric conversion efficiency. Especially under high temperature conditions, the thermoelectric performance of this material is more prominent, which provides the possibility of achieving efficient thermoelectric conversion.

[0037] Embodiment 2

[0038] A method for preparing anion-cation co-doped optimized tin selenide thermoelectric material, the specific operation is as follows:

[0039] Step 1: High-purity raw materials were accurately weighed in the air, including 9.0082 grams of tin powder (with a purity exceeding 99.999%), 5.9918 grams of selenium powder (also with a purity exceeding 99.999%), and 0.075 grams of ZrCl_4 powder (with a purity also exceeding 99.999%). Then, these raw materials were mixed evenly and placed in a double-layer high-purity quartz tube. Under the condition that the vacuum degree reached or was lower than 10^-4Pa, the quartz tube was sealed;

[0040] Step 2: Place the sealed quartz tube in a vertical muffle furnace, heat it to a high temperature of 950°C by setting a heating rate of 92.5°C / hour, and keep it warm for 24 hours at this temperature; after the insulation process is completed, cool the quartz tube to room temperature at the same cooling rate of 92.5°C / hour, thereby obtaining a melt-molded doped sample ingot;

[0041] Step 3: In order to obtain the desired powder material, the ingot was manually ground in air using an agate mortar for 20 minutes to break it into powder, and then the particle size range of the powder was controlled by sieving to be between 10 and 100 nanometers, and the powder was heat-treated under an inert atmosphere (such as argon or nitrogen);

[0042] Step 4: Finally, a graphite mold with an inner diameter of 15 mm and a height of 60 mm was selected, and the processed doped sample powder was placed in it. Spark plasma sintering treatment was carried out under the conditions of sintering temperature of 500°C, applied pressure of 50 MPa, heating rate of 90°C / min, sintering time of 13 minutes and sintering vacuum degree reaching or lower than 4.0 Pa. This step enabled the powder grains to complete the re-orientation, ordered arrangement and recrystallization growth process in a high temperature, high pressure and high vacuum environment, and finally the doped bulk tin selenide-based thermoelectric material was obtained.

[0043] In summary, through high-temperature melt solid-phase reaction and spark plasma sintering treatment, the grains inside the material are reoriented and arranged in order, thereby improving the stability and reliability of the material. This enhanced stability enables the material to maintain stable thermoelectric properties during long-term use and extends the service life of the material.

[0044] Embodiment 3

[0045] A method for preparing anion-cation co-doped optimized tin selenide thermoelectric material, the specific operation is as follows:

[0046] Step 1: In a glove box filled with helium, three high-purity raw materials were accurately weighed: 9.0082 grams of tin powder (purity exceeding 99.999%), 5.9918 grams of selenium powder (purity also exceeding 99.999%), and 0.075 grams of ZrCl_4 powder (purity also reaching more than 99.999%); after these raw materials were fully mixed, they were carefully placed in a double-layer high-purity quartz tube and sealed under strict conditions of a vacuum degree of or below 10^-4Pa;

[0047] Step 2: Next, the sealed quartz tube is transferred to a vertical muffle furnace, and a high-temperature melt solid phase reaction is started. The furnace temperature is gradually raised to 950°C by precisely controlling the heating rate (92.5°C / hour), and the temperature is kept at this temperature for up to 24 hours. After the insulation is completed, the furnace temperature is slowly lowered to room temperature at the same cooling rate of 92.5°C / hour. At this time, a melt-molded tin selenide sample ingot doped with ZrCl_4 is obtained;

[0048] Step 3: In order to convert the ingot into a powder material suitable for further processing, we returned to the glove box and used an agate mortar to manually grind the ingot for 20 minutes until it was broken into fine powder. Then, a graphite mold with an inner diameter of 15 mm and a height of 60 mm was selected to grind the ground ingot into a powder. In the spark plasma sintering equipment, the sintering temperature was set to 500°C, the applied pressure was 50 MPa, the heating rate was 90°C / min, the sintering time was 13 minutes, and the sintering vacuum degree was at or below 4.0 Pa. Under these strict parameters, the powder grains completed the re-orientation, ordered arrangement and recrystallization growth process in a high temperature, high pressure and high vacuum environment. Finally, the bulk tin selenide-based thermoelectric material doped with ZrCl_4 was obtained.

[0049] In summary, the entire preparation process is carried out under strict helium protection, ensuring the purity of the raw materials and the smooth progress of the reaction; at the same time, by precisely controlling parameters such as the heating rate, holding time, cooling rate, and sintering conditions, precise regulation of the material's microstructure and properties is achieved. This controllable and efficient preparation method provides strong support for the large-scale production of high-quality thermoelectric materials.

[0050] Comparative Example 1

[0051] This comparative example shows how to prepare a pure sample of n-type polycrystalline tin selenide-based thermoelectric material SnSe0.95, and gives its performance characterization data. The specific preparation steps are as follows:

[0052] Step 1: In a glove box filled with helium, high-purity tin powder (9.0082 grams, purity exceeding 99.999%) and selenium powder (5.9918 grams, purity also exceeding 99.999%) were accurately weighed, the two raw materials were fully mixed, placed in a double-layer high-purity quartz tube, and sealed and sintered under the condition that the vacuum degree reached or was lower than 10^-4Pa;

[0053] Step 2: Next, the sealed quartz tube is placed in a vertical muffle furnace, heated to 950°C at a heating rate of 92.5°C / hour, and maintained at this temperature for 24 hours for high-temperature melt solid phase reaction. After the reaction is completed, the furnace temperature is lowered to room temperature at the same cooling rate, and a melt-molded SnSe0.95 ingot is obtained;

[0054] Step 3: manually grinding the ingot for 20 minutes using an agate mortar in a glove box to break it into powder, and controlling the particle size of the powder to be between 10 and 100 nanometers by sieving, and heat treating the powder under an inert atmosphere (such as argon or nitrogen);

[0055] Step 4: Finally, a graphite mold with an inner diameter of 15 mm and a height of 60 mm was selected, and the ground powder was filled into it. In the spark plasma sintering equipment, a sintering temperature of 500°C, an applied pressure of 50 MPa, a heating rate of 90°C / min, a sintering time of 13 minutes, and a sintering vacuum of no more than 4.0 Pa were set. Under these conditions, the powder underwent a re-orientation, ordered arrangement, and recrystallization growth process, and finally a pure sample block of n-type polycrystalline tin selenide-based thermoelectric material SnSe0.95 was obtained.

[0056] It should be noted that the main difference between this comparative example and Example 1 is that ZrCl4 doping is not introduced, so a pure SnSe0.95 thermoelectric material is obtained.

[0057] Comparative Example 2

[0058] In this comparative example, a thermoelectric material with a chemical composition of SnSe0.95 plus 0.125 weight percent of ZrCl4 was prepared, which means that the doping content of ZrCl4 was set to x=0.125. The preparation process was carried out in a glove box filled with helium to ensure the purity of the material. High-purity tin powder (9.0082 grams, purity exceeding 99.999%), selenium powder (5.9918 grams, purity exceeding 99.999%) and a trace amount of ZrCl4 powder (0.01875 grams, purity also exceeding 99.999%) were weighed. These raw materials were mixed and used in subsequent synthesis steps.

[0059] Comparative Example 3

[0060] Similar to Comparative Example 2, Comparative Example 3 also prepared tin selenide-based thermoelectric materials, but the doping content of ZrCl4 was different. In this example, the chemical composition was SnSe0.95 plus 0.25 weight percent of ZrCl4, that is, the doping content of ZrCl4 was x = 0.25. The preparation process was also carried out in a helium glove box to ensure an oxygen-free and water-free working environment. The same amount of tin powder and selenium powder as in the previous comparative example was used, but the amount of ZrCl4 powder was increased to 0.0375 grams.

[0061] In short, both Comparative Examples 2 and 3 are about the preparation of n-type polycrystalline tin selenide-based thermoelectric materials with different ZrCl4 doping amounts, wherein the doping amount of Comparative Example 2 is 0.125wt%, while the doping amount of Comparative Example 3 is 0.25wt%.

[0062] By co-doping with Zr4+ and Cl- ions, n-type polycrystalline tin selenide doped samples were successfully prepared, which significantly improved their electrical transport properties, increased carrier concentration and conductivity, while maintaining high mobility and Seebeck coefficient. Combined with spark plasma sintering technology, multi-scale defects were introduced, which significantly reduced the lattice thermal conductivity. Ultimately, a ZT value of up to 1.42 was achieved at 773K, achieving synergistic optimization of thermoelectric performance.

[0063] In summary, the method for preparing tin selenide thermoelectric material with optimized anion and cation co-doping not only significantly improves the electrical transport properties of n-type polycrystalline tin selenide, including carrier concentration, electrical conductivity and Seebeck coefficient, through co-doping with Zr4+ and Cl- anions and cations, and achieves a two-fold increase in the power factor; it also effectively reduces the lattice thermal conductivity by introducing multi-scale defects and nanostructured second phase ZrSn, thereby achieving a double improvement in thermoelectric performance, and ultimately reaching a ZT value of up to 1.42 at 773K.

[0064] In addition, by finely controlling the powder range and adopting the spark plasma sintering process, the grain reorientation and orderly arrangement of the doped sample under high temperature, high pressure and high vacuum conditions are ensured, further optimizing the thermal transport properties and some mechanical properties; at the same time, the stabilizing effect of the ZrSn second phase reduces the deteriorating effect of the second phase Sn on the tin selenide matrix, enhancing the overall stability and reliability of the material, and providing strong support for the practical application of tin selenide thermoelectric materials.

[0065] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material, characterized in that: The following steps are involved: Step 1: First, in a glove box filled with helium, according to the specific needs of the experiment and the atomic mass ratio, the appropriate amount of tin powder, selenium powder and dopant - zirconium tetrachloride powder are accurately weighed out. These raw materials are carefully placed in a high-purity quartz glass tube. Then, a vacuum tube sealer is used to perform a double-layer vacuum sealing process on the quartz glass tube containing the raw materials under extremely high vacuum conditions to ensure the purity and stability of the reaction environment; Step 2: Then put the sealed quartz glass tube into a vertical muffle furnace. At high temperature, these raw materials will undergo a melt-solid phase reaction. When the preset melting program is completed, the sample can be allowed to gradually cool down to room temperature as the furnace cools. In this process, the raw materials will fuse and form a sample ingot doped with specific ions; Step 3: Finally, the molten ingot is placed back into the glove box and manually ground into powder using an agate mortar. The particle size range of the powder is precisely controlled by sieving. Next, the powder is heat treated in an inert atmosphere (such as argon or nitrogen) to remove moisture and residual gas. Subsequently, a graphite mold with a suitable inner diameter is selected to perform spark plasma sintering on the pretreated powder. Finally, a graphite mold with a suitable inner diameter is selected, the ground powder is filled into it, and spark plasma sintering is performed to obtain a preliminary doping-optimized bulk tin selenide-based thermoelectric material.

2. The method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material according to claim 1, characterized in that: The chemical composition of the prepared n-type polycrystalline stannous selenide-based thermoelectric material consists of a mixture of SnSe and ZrCl4, specifically in the form of SnSe0.95+xwt%ZrCl4, wherein the value of x ranges from 0 to 1.

3. The method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material according to claim 1, characterized in that: In step 1, the total weight of the raw materials is controlled between 10 and 20 grams, and the purity of the raw materials exceeds 99.9%. The raw materials must be processed under high vacuum conditions during the vacuum sealing process, and the vacuum degree must be lower than or equal to 10^-2Pa.

4. The method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material according to claim 1, characterized in that: In step 1, during the high-temperature melt solid phase reaction stage, the reaction temperature is precisely controlled between 900 and 1000°C, the insulation time is between 20 and 30 hours, and the heating and cooling rate is controlled between 50 and 100°C / hour.

5. The method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material according to claim 1, characterized in that: In step 2, during the ingot processing stage after melt forming, the ingot needs to be manually ground using an agate mortar in a glove box, and the grinding time needs to be controlled between 10 and 30 minutes.

6. The method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material according to claim 1, characterized in that: In step three, the ground powder needs to be sieved to control its particle size range to be between 10 and 1000 nanometers. The inner diameter of the graphite mold used in the spark plasma sintering should be in the range of 10-20 mm, and the mold height should be in the range of 50-70 mm.

7. The method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material according to claim 1, characterized in that: In step three, the process parameters of the spark plasma sintering process need to be strictly controlled, the sintering temperature should be between 450 and 550°C, the applied pressure should be between 45 and 55 MPa, the heating rate should be between 50 and 100°C / minute, the sintering time should be between 10 and 15 minutes, and the sintering process should be carried out under a vacuum degree less than or equal to 10.0 Pa.

8. The method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material according to claim 1, characterized in that: In step three, the heat treatment temperature ranges from 100 to 300° C., and the insulation time ranges from 1 to 5 hours.

9. The method for preparing an anion-cation co-doped optimized tin selenide thermoelectric material according to claim 1, characterized in that: Prepared from the content described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of zirconium silicate coated iron oxide red for ceramic ink-jet printing

    CN110655807A

  • Thermoelectric materials and a process for the preparation thereof

    CN111788704A

  • Heterogeneous doped tin selenide thermoelectric material and synthesis method thereof

    CN115498093A

  • Preparation method for improving thermoelectric performance of tin selenide base by combining component regulation with mesoscopic ordered regulation

    CN118834070A

  • Manufacturing of workpieces having nanostructured phases from functionalized powder feedstocks

    US20200276638A1